RELATIONSHIP OF BOARD ATTRIBUTES WITH SUKUK RANKING IN INDONESIA AND COMPANY CHARACTERISTICS AS CONTROL VARIABLES - Putri Aryo JFK; Harjum Muharam (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study is to determine the effect of the board's attributes from the corporate governance mechanism on the rating of sukuk in Indonesia. This study was conducted to see whether companies that implement corporate governance correctly get higher ratings than companies with poor implementation of corporate governance. The method used is a quantitative research method with ordinal logistic regression test equipment. The research sample was obtained by using purposive sampling technique. The results showed that CEO tenure, board of commissioners size, firm size, and profitability had a significant positive effect on sukuk ratings. The size of the board of directors and leverage have a significant negative effect on sukuk ratings, while the proportion of independent commissioners has no significant effect on the sukuk rating. This study only covers the issuance of sukuk in Indonesia, and one rating agency. Nothing can compare to the issue of sukuk abroad. Keywords: term of office of CEO, board of directors, board of commissioners, proportion of independent commissioners, sukuk ratings